Development of the transfer of short story vehicles to short films as a learning innovation for digital literature courses - Rianto, Rianto; Nuryanto , Tato; Young Soo, Kim (BAHASTRA, 2024)
This research aims to examine the development of transferring short stories to short films as an innovation in learning Digital Literature courses. The method used is the Research and Development (R&D) model with the ADDIE approach which consists of five stages: analysis, design, development, implementation, and evaluation. At the analysis stage, needs identification is carried out through literature studies, observations, and interviews with lecturers and students to determine current needs and problems in literature learning. The design stage includes material planning, making storyboards and short film scripts, and evaluation design. The development stage includes short film production, the creation of learning materials, initial trials, and revisions based on feedback. Implementation is carried out by involving students in the learning process using short films as a learning medium. The research results show that switching from short stories to short films can increase students' understanding of literary works and provide practical skills in digital media production. This research is expected to offer new insights for teachers and students about the potential for integrating technology in literature learning, as well as motivating the development of more creative and interactive learning methods in the future.